2019
DOI: 10.3390/nano9121740
|View full text |Cite
|
Sign up to set email alerts
|

Composites Based on Nanoparticle and Pan Electrospun Nanofiber Membranes for Air Filtration and Bacterial Removal

Abstract: Often, solid matter is separated from particle-laden flow streams using electrospun filters due to their high specific surface area, good ability to capture aerial particulate matter, and low material costs. Moreover, electrospinning allows incorporating nanoparticles to improve the filter’s air filtration efficiency and bacterial removal. Therefore, a new, improved polyacrylonitrile (PAN) nanofibers membrane that could be used to remove air pollutants and also with antibacterial activity was developed. We eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 65 publications
1
47
1
7
Order By: Relevance
“…The nanofiber membrane showed superior performance in removal of color and turbidity compared to the microporous membrane and supported extended stability and shelf-life of beverage products. Bortolassi et al [ 42 ] fabricated a PAN-based composite nanofiber filtration membrane using an electrospinning method and reported mean nanofiber diameters of 292 ± 6 nm, 242 ± 5 nm, and 289 ± 5 nm for Ag/PAN, TiO 2 /PAN, and ZnO/PAN nanofibrous membranes, respectively, which formed mean pore sizes of 1.12 ± 0.10 µm, 1.45 ± 0.10 µm, and 2.03 ± 0.10 µm, respectively. Also, they observed that Ag/PAN electrospun nanofibrous membranes show the highest permeability than other counterparts (TiO 2 /PAN, ZnO/PAN) due to reduced pressure drop (68.13 Pa) across the filter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanofiber membrane showed superior performance in removal of color and turbidity compared to the microporous membrane and supported extended stability and shelf-life of beverage products. Bortolassi et al [ 42 ] fabricated a PAN-based composite nanofiber filtration membrane using an electrospinning method and reported mean nanofiber diameters of 292 ± 6 nm, 242 ± 5 nm, and 289 ± 5 nm for Ag/PAN, TiO 2 /PAN, and ZnO/PAN nanofibrous membranes, respectively, which formed mean pore sizes of 1.12 ± 0.10 µm, 1.45 ± 0.10 µm, and 2.03 ± 0.10 µm, respectively. Also, they observed that Ag/PAN electrospun nanofibrous membranes show the highest permeability than other counterparts (TiO 2 /PAN, ZnO/PAN) due to reduced pressure drop (68.13 Pa) across the filter.…”
Section: Resultsmentioning
confidence: 99%
“…They reported that nylon nanofibrous membranes completely removed yeast ( S. cerevisiae) and mixed bacterial cultures ( F. johnsoniae and I. fluviatilis ); whereas, 3 and 5 log reductions could be achieved in the beer suspensions fortified with I. fluviatilis and F. johnsoniae, respectively. Bortolassi et al [ 42 ] observed the efficient removal of bacterial cells using the composite-based Ag/PAN nanofiber filtration membrane and reported the reduction of the bacterial load from 10 8 CFU/mL to 10 3 CFU/mL while filtration through the Ag/PAN nanofibrous membrane. In another study, Ma et al [ 46 ] developed functionalized PAN electrospun membranes by a surface modification process for the removal of bacteria and viruses.…”
Section: Resultsmentioning
confidence: 99%
“…It was proposed that the permanent dipole orientation of SiO 2 helps in trapping more charges and presents more stability, providing a chance to adsorb more target particles and pathogens. A recent study demonstrated the fabrication of novel PAN membranes loaded with ZnO, TiO 2 and AgNPs by electrospinning, and the filtration performances were assessed by NaCl filtration [ 91 ]. The TiO 2 _F filter displayed the highest filtration efficiency (≈100%), whereas the Ag_F filter showed the highest QF (≈0.06 Pa −1 ).…”
Section: Recent Advancesmentioning
confidence: 99%
“…Air filtration has become the focus of global environmental protection [1][2][3][4]. The existence of fine particulate matter (PM) has posed a great threat to public health [5,6].…”
Section: Introductionmentioning
confidence: 99%